THE VALIDITY OF OWNERSHIP RIGHTS TO LAND BY FOREIGN CITIZEN THROUGH A NOMINEE AGREEMENT - Wulandari, Eka (Communale Journal, 2024)
This research aims to determine the validity of ownership rights to land by foreign citizens (WNA) through nominee agreements. A Nominee Agreement, commonly known as a name transfer or name borrowing agreement, is an agreement made on behalf of another party. The practice of nominee agreements still often occurs, even though foreigners do not have ownership rights by what is regulated in statutory regulations. Foreigners did this to control ownership rights to land in Indonesia and gain personal gain. No specific regulations govern nominee agreements, so law enforcement is not optimal. This research uses a normative juridical method with a statutory and case approach. The research results show that the nominee agreement entered into by foreigners is invalid because it needs to meet the objective elements of the requirements, namely lawful reasons that are already regulated in Article 1320 in the Civil Code.